The impact of cigarette dependence severity on disease outcomes and depression in ankylosing spondylitis - Dülger, Seyhan; Aykurt Karlıbel, İlknur and Yıldız, Tekin and Altan, Lale and Şengören Dikiş, Özlem and Kasapoğlu Aksoy, Meliha (The European Research Journal, 2018)
Introduction: Ankylosing spondylitis (AS) is a chronic systemic inflammatory disease. Smoking plays a role in AS pathogenesis and causes difficulties in its treatment. The aim of this study is to investigate the association of disease activity, functional status, spinal mobility, depression, chest expansion, pain, fatigue, quality of life, respiratory function with cigarette dependence severity in patients with AS. Methods: The study included 71 patients diagnosed as AS. Patients were evaluated on questionnaires and examination scales specific to assessment of AS. The results were compared using the SPSS-23 software. Results: Out of the total 71 patients, 40 (56.3%) were smokers, 31 (43.7%) were non-smokers. There were no significant differences between the smokers and the non-smokers with respect to the median values in Bath Ankylosing Spondylitis Disease Activity Index, Bath Ankylosing Spondylitis Metrology Index (BASMI), Bath Ankylosing Spondylitis Functional Index, Ankylosing Spondylitis Quality of Life questionnaire, Short Form 36 (SF-36), chest expansion, the fingertip-to-floor test and Beck Depression Inventory (p > 0.05). However, there were significant differences when comparing the median scores on BASMI (p = 0.036), SF-36 physical role strength (p = 0.004) and the chest expansion (p = 0.015) of the smoker patients placed in the three Fagerström Test for Nicotine Dependence (FTND) subgrouping. Conclusion: AS patients with smoking have elevated FTND scores and worse values for test of disease activity and quality of life.